La categoría oposición política: Reflexiones para su conceptualización (2014)
This paper presents a conceptual reflection about political opposition category, fundamental in any context to ensure that democracy is consolidated form of government. One of the thesis of this article is that the concept is framed in social and historical processes which in turn have shaped ways of seeing and thinking about politics in general. Thus, the work is divided into two parts: the first, a sociological and historical dialogue with Aristotle, Hobbes and Mouffe is exerted on the concept of politics to understand it as a constant tension between the exercise and the dispute over the power; derivative thereof, the second part exposes the political opposition category and modes as often is assumed. © 2014 Universidad Nacional de Colombia. All rights reserved.